ASSESSMENT OF EFFECTIVENESS OF SODIUM-GLUCOSE TRANSPORT PROTEIN-2 INHIBITORS IN TYPE-2 DIABETIC PATIENTS IN A TERTIARY CARE HOSPITAL – A LONGITUDINAL PROSPECTIVE STUDY - VEERENDRA KUMAR; STV RAGHAVAMMA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The main aim of the study was to assess the effectiveness of the sodium-glucose transport protein-2 inhibitors (SGLT-2i) in type 2 diabetic patients. Methods: This was a prospective and longitudinal study conducted in a tertiary care center. During the study period, the data were collected from 200 diabetic patients, out of which 80 patients were followed up. Data collection form and informed consent were obtained from each patient. Results: Out of 200 patients, 84 (42%) were female while 114 (58%) being male aged between 50 and 70 years had a higher prevalence of type 2 diabetes mellitus. Dapagliflozin was administered to 54 (67.5%) of the 80 patients, while empagliflozin was administered to 26 (32.5%). A total of 32 patients receiving dapagliflozin had baseline glycated hemoglobin (HbA1c) values of 7.6–9.0%, followed by >9% (n=16) and 6.5–7.5% (n=6), respectively. Sixteen patients receiving empagliflozin had baseline HbA1c values of 7.6–9.0%, followed by >9 (n=8) and 6.5–7.5% (n=2). After the start of the medicine, an average of gradual reduction of HbA1c was found to be 1.47%, while the study focused on the same. Conclusion: SGLT-2i showed its action in lowering the blood glucose in patients who were adherent to the treatment regimen along with diet and exercise.